Priming of soil organic carbon induced by sugarcane residues and its biochar control the source of nitrogen for plant uptake: A dual 13C and 15N isotope three-source-partitioning study. (July 2020) - Weng, Zhe (Han); Liu, Xihui; Eldridge, Simon; Wang, Hailong; Rose, Terry; Rose, Mick; Rust, Josh; Singh, Bhupinder Pal; Tavakkoli, Ehsan; Tang, Caixian; Ou, Huiping; Van Zwieten, Lukas
Abstract: Sugarcane ( Saccharum spp.) farming systems globally have largely transitioned away from burning the crop prior to harvest. Harvesting the sugarcane crop 'green' results in large volumes of biomass residues being left on the soil. Despite this, there is little evidence for increased soil organic carbon stocks. We investigated the role of surface application or incorporation (0–200 mm soil layer) of harvest residues (15 t dry weight residues ha −1 ) and its biochar (5.4 t ha −1 based on the quantity of resource recovered after pyrolysis) on the priming of native soil organic carbon (SOC), the mineralisation of the organic amendments and the source of crop nitrogen (N) uptake (soil, organic amendment or urea). All treatments received urea at 180 kg N ha −1 . To achieve the separation of C and N sources, dual 13 C and 15 N-enriched sugarcane residues and corresponding biochar (350 °C) were used in an 84-d controlled environment study. A three-pool isotope mixing model, utilising two levels of 13 C enrichment in residue (16.6‰ and 23.8‰) and biochar (16.8‰ and 24.1‰), was also applied to partition the C from three sources: 1) root respiration, 2) organic amendment mineralisation, and 3) SOC priming. The SOC mineralisation was increased following both surface-applied and incorporated residues, over the nil organic amendment (control) by 72.3 and 78.3 CO2 –C m −2 respectively over 84 days. In contrast, biochar lowered the mineralisation of SOC by 62.9 g CO2 –C m −2 compared to the control. The cumulative mineralisation of sugarcane residue biochar (18.9 g CO2 –C m −2 ) was lower ( P  = 0.03) than surface applied residue (50.1 g CO2 –C m −2 ) and incorporated residue (71.9 g CO2 –C m −2 ) over the study period. While there were no differences in total crop N uptake between the organic-amended soils and the control, the source of N was significantly different. The sugarcane plants utilised 31.0% and 29.4% of the supplied urea N in the nil organic-amended control and biochar treatment, respectively. This was significantly reduced to 24.8% and 20.6% in the surface residue and incorporated residue treatments, respectively. In comparison, the plant uptake of N derived from the organic amendments was 27.8%, 15.4% and 6.4% from incorporated residues, surface-applied residues and biochar, respectively ( P  < 0.001). Results suggest that the increased mineralisation of SOC, partly driven by the high C:N ratio (73:1) and the unbalanced nutrient stoichiometry may lead to low SOC accumulation from surface residue application and that sugarcane residue biochar results in SOC stabilisation and an increase in the use efficiency of fertiliser N in sugarcane systems. Highlights: Dual 13 C and 15 N study allowed differentiation between 3 C pools and plant N source. Return of sugarcane residues to the field resulted in positive priming of SOC. Sugarcane residue biochar resulted in the stabilisation of SOC. Biochar resulted in greater fertiliser 15 N uptake efficiency cf. residue retention. Residue retention resulted in greater plant uptake of N from SOC mineralisation.